Preparation, characterization and featuring of an inclusion complex of nerol with Î²-cyclodextrin - CoÃªlho, Mayara; da Silva, Herlane; Islam, Muhammad; Viana, Vicente; Melo-Cavalcante, Ana AmÃ©lia (International Journal of Medicine, 2017)
Nerol is an acyclic type monoterpene with important biological activities. However, the low solubility in aqueous media is a limiting factor for its user. Cyclodextrins have been widely used in order to improve the solubility, stability and bioavailability of nonpolar molecules through the formation of inclusion complexes. Thus, the present study consists in the development of nerol inclusion complex in combination with the Î²-cyclodextrin (Î²-CD) followed by characterizing by thermal analysis and spectrophotometric absorption in the infrared (FTIR). The results suggest a complexation of nerol with Î²-CD having detours and changed the intensity of various bands. The thermo gravimetric curve of CI found to indicate an output of solvating water molecules from the complex cavity formed for replacement of drug molecules probably included. Thus, it is concluded a possibility to obtain inclusion complexes of nerol monoterpene with Î²-CD, which will increase its solubility and facilitate delivery process.